2022
DOI: 10.1098/rsos.220124
|View full text |Cite
|
Sign up to set email alerts
|

Randomness in the choice of neighbours promotes cohesion in mobile animal groups

Abstract: Classic computational models of collective motion suggest that simple local averaging rules can promote many observed group-level patterns. Recent studies, however, suggest that rules simpler than local averaging may be at play in real organisms; for example, fish stochastically align towards only one randomly chosen neighbour and yet the schools are highly polarized. Here, we ask—how do organisms maintain group cohesion? Using a spatially explicit model, inspired from empirical investigations, we show that gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…It has also been shown that sheep select interaction neighbors [62]. To incorporate this cognitive constraint in our model, we introduce a key modification — sheep perceives a limited number of its nearest neighbors, among which only k have an impact on its behavior [63].…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that sheep select interaction neighbors [62]. To incorporate this cognitive constraint in our model, we introduce a key modification — sheep perceives a limited number of its nearest neighbors, among which only k have an impact on its behavior [63].…”
Section: Resultsmentioning
confidence: 99%
“…In our model, each agent is characterised by its orientation, e i = (cos θ i , sin θ i ), position x i and moves at a constant speed, v. Agents move within a box of length L with periodic boundary conditions, and we update the positions of agents every ∆t. Recent studies have emphasised the role of the probabilistic nature of animal interactions on collective motion [44,69,70]. We incorporate this via asynchronous interactions among agents and choice of neighbours [70], as described below.…”
Section: Local Alignment Models With Asynchronous Update Rules For Co...mentioning
confidence: 99%
“…In other words, the schooling of fish is a consequence of the noise associated with small-sized groups, and hence is termed noise-induced schooling. Similarly, other group characteristics such as mechanical properties [38][39][40][41][42] and cohesion have also been identified as a consequence of stochastic effects [43,44]. Intrinsic noise could also be important in evolutionary dynamics that shapes collective motion of finite flocks [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…Some models have been proposed that, by defining a set of interactions between the individuals comprising a school of fish, we are able to reproduce the collective behaviours of schools of fish that are most frequently observed in nature. Such models are commonly referred to as individual-based or agentbased models [5,[7][8][9]: in them, the evolution of position and velocity of each individual is governed by a set of differential equations [10][11][12][13][14][15][16][17] or a set of difference equations [4,[18][19][20][21][22][23][24][25][26][27][28][29][30] at discrete instants of time. Despite the simplicity of the interactions included in these models, they have been successful in replicating collective behaviours with good accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there are models in which the collective behaviours already mentioned emerge even in the absence of orientation [11,12,14,16,44] or in the presence of attraction alone [16,23,25,27]. Finally, it is worth noting that in many works, the investigation was performed by restricting the school of fish to moving in one plane [9][10][11][12][13][14][15][16][17]22,23,26,27,29,30,45] and setting precise initial conditions to start its movement [10,12,13,29,45].…”
Section: Introductionmentioning
confidence: 99%